Esposas en guerra (Esposas del ciclo troyano) (Heroínas de la mitología griega II) - Esteban Santos, Alicia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
This paper deals with the most representative wives in the Trojan War (Helen, Andromache, Clytemnestra and Penelope –famous epic and tragic heroines– and also Laodamia), focussing on the family aspect and their relationship and confrontation with the respective husband, and especially on their prototypical function, because they exemplify almost all possible patterns of wives (with different analogies and oppositions between them) and behaviours in a critical situation, during a war. They also represent the personification of all kind of horrors that a war brings, as the Trojan War is the prototypical WAR for ever and ever.